French visual culture and the making of medieval theater - Weigert, Laura (Cambridge University Press, 2015)
This book revives what was unique, strange and exciting about the variety of performances that took place in the realms of the French kings and Burgundian dukes. Laura Weigert brings together a wealth of visual artifacts and practices to explore this tradition of late medieval performance located not in 'theaters' but in churches, courts, and city streets and squares. By stressing the theatricality rather than the realism of fifteenth-century visual culture and the spectacular rather than the devotional nature of its effects, she offers a new way of thinking about late medieval representation and spectatorship. She shows how images that ostensibly document medieval performance instead revise its characteristic features to conform to a playgoing experience that was associated with classical antiquity. This retrospective vision of the late medieval performance tradition contributed to its demise in sixteenth-century France and promoted assumptions about medieval theater that continue to inform the contemporary disciplines of art and theater history